3D Printing by Multiphase Silicone/Water Capillary Inks. Issue 30 (7th June 2017) - Roh, Sangchul; Parekh, Dishit P.; Bharti, Bhuvnesh; Stoyanov, Simeon D.; Velev, Orlin D.
Abstract : 3D printing of polymers is accomplished easily with thermoplastics as the extruded hot melt solidifies rapidly during the printing process. Printing with liquid polymer precursors is more challenging due to their longer curing times. One curable liquid polymer of specific interest is polydimethylsiloxane (PDMS). This study demonstrates a new efficient technique for 3D printing with PDMS by using a capillary suspension ink containing PDMS in the form of both precured microbeads and uncured liquid precursor, dispersed in water as continuous medium. The PDMS microbeads are held together in thixotropic granular paste by capillary attraction induced by the liquid precursor. These capillary suspensions possess high storage moduli and yield stresses that are needed for direct ink writing. They could be 3D printed and cured both in air and under water. The resulting PDMS structures are remarkably elastic, flexible, and extensible. As the ink is made of porous, biocompatible silicone that can be printed directly inside aqueous medium, it can be used in 3D printed biomedical products, or in applications such as direct printing of bioscaffolds on live tissue. This study demonstrates a number of examples using the high softness, elasticity, and resilience of these 3D printed structures. Abstract : An efficient technique for fabricating multiphase 3D printable polydimethylsiloxane (PDMS) ink is introduced. The ink is a capillary suspension consisting of PDMS microbeads (cured), PDMS liquid precursor (uncured), and water (continuous phase). Upon curing, the printed PDMS ink becomes highly porous, elastic, flexible, and extensible, which promises industrial applications such as biomedical products and bioscaffolds.